Key performance indicators for the golf swing in elite collegiate golf athletes: an exploratory study - Johnson, Q.; Yang, Y.; Ziola, K.; Sun, D.; Moore, J.; Sutton, P.; Fry, A.; Smith, D. (International Journal of Strength and Conditioning, 2025)
Golf swing performance has been found to be influenced by health status, physical fitness, and technical abilities. However, as the sport becomes more competitive, athletes and coaches regularly seek novel approaches to optimizing athletic performance. This study sought to identify key performance indicators that are significantly related to golf club head speed within an elite collegiate golf population. Height, weight, vertical and lateral jump, upper-body rotational velocity, club head speed, and swing kinematics for 21 NCAA Division I female (n = 11) and male (n = 10) golf athletes were collected for analysis. Significant differences between female and male athletes were observed for measures of anthropometry, jumping ability, upper-extremity rotational velocity as well as clubhead speed (p < 0.05). Of particular interest were findings that suggest load-velocity profiling as a novel (for the sport of golf) but useful tool to support individualized golf swing profiling and technical improvement approaches. However, no significant differences between groups were observed for any rotational kinematic measure (p > 0.05). Interestingly, a novel assessment of swing kinematics revealed that peak rotational velocities at specific loads relative to an athlete`s body mass were discovered to have a significantly moderate positive correlation with fast club head speed (p < 0.05). Altogether, these findings can be utilized by sports performance professionals to improve the assessment, development, and performance capabilities of golfers interested in enhancing their clubhead speed.